2020
DOI: 10.1021/acsnano.0c02831
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Molybdenum Diselenide Helical Nanorod Arrays for High-Performance Aluminum-Ion Batteries

Abstract: The rechargeable aluminum-ion battery (AIB) is a promising candidate for next-generation high-performance batteries, but its cathode materials require more development to improve their capacity and cycling life. We have demonstrated the growth of MoSe 2 three-dimensional helical nanorod arrays on a polyimide substrate by the deposition of Mo helical nanorod arrays followed by a low-temperature plasma-assisted selenization process to form novel cathodes for AIBs. The binder-free 3D MoSe 2 -based AIB shows a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 67 publications
0
47
0
Order By: Relevance
“…The intense peaks centered at 1334 and 1584 cm À 1 were ascribed to pure CFP and the peaks at 237 and 282 cm À 1 were assigned to the A 1g and E 1 2g specific modes of 2H-MoSe 2 , respectively. [30] The E 1 2g peak was much weaker than the A 1g peak, which is characteristic of the edge-abundant structure of MoSe 2 nanosheets. Unlike the A 1g and E 1 2g peaks of raw and annealed MoSe 2 , those of P-doped MoSe 2 were redshifted by approximately 2.6 cm À 1 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The intense peaks centered at 1334 and 1584 cm À 1 were ascribed to pure CFP and the peaks at 237 and 282 cm À 1 were assigned to the A 1g and E 1 2g specific modes of 2H-MoSe 2 , respectively. [30] The E 1 2g peak was much weaker than the A 1g peak, which is characteristic of the edge-abundant structure of MoSe 2 nanosheets. Unlike the A 1g and E 1 2g peaks of raw and annealed MoSe 2 , those of P-doped MoSe 2 were redshifted by approximately 2.6 cm À 1 .…”
Section: Resultsmentioning
confidence: 94%
“…The Raman spectra of the as‐prepared P‐doped MoSe 2 /CFP, annealed MoSe 2 /CFP, raw MoSe 2 /CFP, and CFP are presented in Figure 1(c). The intense peaks centered at 1334 and 1584 cm −1 were ascribed to pure CFP and the peaks at 237 and 282 cm −1 were assigned to the A 1g and E 1 2g specific modes of 2H‐MoSe 2 , respectively [30] . The E 1 2g peak was much weaker than the A 1g peak, which is characteristic of the edge‐abundant structure of MoSe 2 nanosheets.…”
Section: Resultsmentioning
confidence: 97%
“…Here the limited time and the large polarization indicated that the Al‐ions intercalation rarely happened, which were in good accordance with characteristics of high‐valent ions storage mechanism. [ 22,34 ] The results indicate that the Al 3+ insertion/extraction is a relatively slow kinetic reaction process that only happened at lower current density processes. Compared with the same tests in 1.2 m H 2 SO 4 electrolyte as shown in Figure S4, Supporting Information, the electrodes displayed higher capacitance in Al 3+ electrolyte than H + electrolyte at low current densities due to the three‐electrons transfer.…”
Section: Resultsmentioning
confidence: 99%
“…[ 175 ] Table 3 summarizes the energy storage performance of different 2D materials in vertically aligned orientation as electrodes of Li, Na, and Al batteries. [ 123,211,175,178–194 ] SnS 2 @C anode delivered an initial discharge and charge capacities of 1851 and 1156 mAh g –1 as compared to the lower values of 1304 and 755 mAh g –1 for pure SnS 2 anode. The reported coulombic efficiency of the SnS 2 @C anode was 62.5% as compared to 57.9% for pure SnS 2 with high stability after 200 cycles.…”
Section: Applications Of Vertically Aligned 2d Materialsmentioning
confidence: 86%